Relationship between Emotional Intelligence and Self Control in Water Polo Atheles - Karina Aditya; Komarudin; Mochamad Yamin Saputra; Geraldi Novian (Universitas Negeri Semarang, 2025)
Water polo is a sport that involves significant physical contact between players. This sometimes makes it difficult for athletes to control their emotions in the game. As a result, athletes often take actions that are detrimental to themselves, the team, and even the opponent. This problem ultimately results in athletes not being able to achieve their best performance. Therefore, good self-control is needed in this sport. Emotional intelligence allows athletes to manage emotions well. This research aims to examine the relationship between emotional intelligence and self-control in water polo athletes. The Descriptive method with a quantitative approach was used in the study involving 20 water polo athletes from Club Tirtamerta Bandung. The instruments used in this study were a trait emotional intelligence questionnaire short form of (TEIQUE-SF) and a brief self-control scale (BSCS) given once to the sample. The results showed that there is a significant relationship between emotional intelligence and self-control in water polo athletes. This is indicated by a large correlation between variables of 0.023 (p <0.050), which means emotional intelligence and self-control have a strong relationship. This study concludes that emotional intelligence has a significant relationship with self-control in water polo athletes, with that the hypothesis that has been proposed is accepted and stated that there is a significant positive relationship between the two variables. Thus it is recommended to focus more attention on the emotional intelligence of athletes during the training stage so that it is expected that the level of self-control in water polo athletes will also increase.